(Co-)pyrolytic performances and by-products of textile dyeing sludge and spent mushroom substrate. (10th July 2020) - Huang, Jianli; Liu, Jingyong; Chang, Kenlin; Buyukada, Musa; Evrendilek, Fatih
Abstract: The (co-)pyrolysis of textile dyeing sludge and spent mushroom substrate was conducted to characterize their thermal behaviors and by-products. The devolatilization of textile dyeing sludge mainly occurred between 150 and 500 °C, while the decomposition of inorganic matter as well as the secondary cracking of coke and tar happened between 500 and 1000 °C. The addition of spent mushroom substrate increased the release rate at the devolatilization stage of textile dyeing sludge and their blends due to its higher volatiles content. The enhanced co-pyrolysis performance occurred mainly at the high temperature. The melting of inorganic matter was enhanced with the temperature rise but weakened with the addition of spent mushroom substrate. Sulfur mainly existed as sulfate in textile dyeing sludge and as organic sulfur in spent mushroom substrate. With the temperature rise, nitrogen-containing compounds formed more stable compounds. Spent mushroom substrate promoted the formation of nitrogen oxides by converting nitrogen to an inactive form. Sulfates were decomposed at high temperatures partially turning into sulfide. 30% spent mushroom substrate increased the relative sulfate content at 800 °C and fixed sulfur into inorganic compounds. The relative contents of aromatics, and nitrogen-containing compounds rose in the bio-oils, whereas alkanes fell with the elevated temperature. Spent mushroom substrate enhanced the formation of aromatics and reduced the yields of nitrogen-containing compounds, and acidic volatiles. The co-pyrolysis appeared to improve the bio-oil quality and the pyrolytic performance of textile dyeing sludge. Graphical abstract: Image 1 Highlights: (Co-)pyrolysis of textile dyeing sludge and spent mushroom substrate were studied. Textile dyeing sludge degraded fastest at 718.8 °C due to its high ash content. Nitrogen and sulfur mainly existed as protein and sulfate in textile dyeing sludge. Co-pyrolysis increased quaternary-N and sulfates in residuals. The addition of spent mushroom substrate yielded more aromatics and less acids.